2021
DOI: 10.1192/j.eurpsy.2021.24
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of post-traumatic stress symptoms among people influenced by coronavirus disease 2019 outbreak: A meta-analysis

Abstract: Background. As one of the most widely researched consequence of traumatic events, the prevalence of post-traumatic stress symptoms among people exposed to the trauma resulting from coronavirus disease 2019 (COVID-19) outbreak varies greatly across studies. This review aimed at examining the pooled prevalence of post-traumatic stress symptoms among people exposed to the trauma resulting from COVID-19 outbreak. Methods. Systematic searches of databases were conducted for literature published on PubMed, EMBASE, W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 106 publications
7
48
4
Order By: Relevance
“…The total score is calculated by adding together the response value of each item, with higher scores indicating more severe levels of depressive, anxiety, and stress symptoms. The score at the DASS-depression subscale (e.g., "I felt that I had nothing to look forward to") is divided into normal (0-9), mild (10)(11)(12), moderate (13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The score at the DASS-anxiety subscale (e.g., "I was worried about situations in which I might panic and make a fool of myself") is divided into normal (0-6), mild (7)(8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe anxiety .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total score is calculated by adding together the response value of each item, with higher scores indicating more severe levels of depressive, anxiety, and stress symptoms. The score at the DASS-depression subscale (e.g., "I felt that I had nothing to look forward to") is divided into normal (0-9), mild (10)(11)(12), moderate (13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe depression (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). The score at the DASS-anxiety subscale (e.g., "I was worried about situations in which I might panic and make a fool of myself") is divided into normal (0-6), mild (7)(8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe anxiety .…”
Section: Methodsmentioning
confidence: 99%
“…The score at the DASS-anxiety subscale (e.g., "I was worried about situations in which I might panic and make a fool of myself") is divided into normal (0-6), mild (7)(8)(9), moderate (10)(11)(12)(13)(14), severe (15)(16)(17)(18)(19), and extremely severe anxiety . The score at the DASS-stress subscale (e.g., "I tended to over-react to situations") is divided into normal (0-10), mild (11)(12)(13)(14)(15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25)(26), severe (27)(28)(29)(30)(31)(32)(33)(34), and extremely severe stress (35)(36)(37)(38)(39)(40)(41)(42).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age and gender have been frequently reported as factors associated with mental health problems during the COVID-19 pandemic. Evidence shows that younger adults (< 40 years old) are generally at higher risk of experiencing higher levels of depression and anxiety amidst the pandemic [7,8,19,20], while older adults may be more susceptible in experiencing posttraumatic stress symptoms [21]. Being a woman has also been reported as a risk factor of experiencing higher depression, anxiety and posttraumatic stress symptoms during this pandemic [8,19,20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the global prevalence estimate was 24.1% for post-traumatic stress symptoms. Another similar articles reported the pooled prevalence of post-traumatic stress symptoms was 28.34% [ 14 ] and 21.94% [ 27 ]. The research mentioned above showed that under the epidemic situation, the general population were at a high level of PTSD across countries and regions, suggesting the attention to PTSD related to COVID-19 should be increased globally and identifying related risk factors in terms of reducing the mental health burden of COVID-19 is crucial.…”
Section: Discussionmentioning
confidence: 99%